Meta-Analysis the Effectiveness of Ivermectin Use on the Length of Stay in Inpatients of COVID-19 - Wijayanto, Masromi Hendria; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: COVID-19 is a common problem in global health. COVID-19 is a disease that infects the respiratory tract caused by the Coronavirus virus. Symptoms range from mild to severe and life-threatening pneumonia can occur. At the beginning of the PSBB, information circulated that Ivemectin could treat COVID-19 infections. Ivermectin is an antiparasitic drug that can be used as prophylaxis and therapy for coronavirus disease 2019. Ivermectin is an alternative therapy for COVID-19 because there is a previous drug, chloroquine, which can be used to treat COVID-19. This study aims to estimate the effectiveness of Ivermectin on the duration of hospitalization of patients with COVID-19 based on the results of previous similar studies.Subjects and Method: This study is a meta-analysis with the following PICO, population: COVID-19 patients. Intervention: ivermectin. Comparison: standard therapy. Outcome: shorter duration of hospital stay. Meta-analyses and systematic studies using the PubMed, Scopus, Scholar, Springlink, Cochrane, Clinical Key, and Science Direct databases. Keywords using Ivermectin AND RCT AND COVID-19 AND “Coronavirus Disease” AND “NCOV disease” AND “COVID-19 treatment”. The article under study is a full-text article with a randomized controlled clinical trial (RCT) study design. Articles were collected using PRISMA diagrams and analyzed using Review Manager 5.3.Results A total of 9 Randomized Control Trial (RCT) studies from Europe, America, Asia and Africa were selected for systematic review and meta-analysis. COVID-19 patients receiving Ivermectin therapy decreased the duration of hospital stay by 1.52 units compared to standard therapy and this result was statistically significant (SMD= -1.52; 95% CI= -2.34 to -0.70; p= 0.003).Conclusion: Ivermectin can reduce the duration of hospital stay for COVID-19 patients.Keywords: COVID-19, ivermectin, duration hospital stayCorrespondence: Masromi Hendria Wijayanto. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: masromihendria@gmail.com. Mobile: 0895402471549.Indonesian Journal of Medicine (2022), 07(02): 200-208https://doi.org/10.26911/theijmed.2022.07.02.08